Fleksibilitas Tindak Tutur Direktif pada Proses Perdagangan di Pasar Tradisional Kota Jambi - Wahyu Kurniawan; Akhyaruddin Akhyaruddin; Adiopenta Puba; Herman Budiyono; Kamarudin Kamarudin (Jurnal Bahasa dan Sastra, 2023)
A typical traditional society uses a unique way of communication. In the context of buying and selling situations, between buyers and sellers often use vague, ambiguous and mysterious utterances. The purpose of this study is to identify the various directive speech acts and the functions of speech acts in the trading process set in traditional markets. This type of research is a qualitative descriptive research with the aim of obtaining an objective description of the speech of traders and buyers in the trading process. The listening method, which is equipped with note-taking techniques and recording techniques, is used to collect research data. For the data analysis method, distribution and equivalent methods were used to answer each research variable. The types of directive speech acts found include directive requests, directive orders, directive questions, directives of advice, and directives of giving permission. The most dominant types of directive speech acts that appear are directive speech acts of asking questions and giving permission. The functions of speech acts that occur in the trading process at Aur Duri Market, Jambi City, include communicating factual information, disclosing intellectual information, expressing emotional attitudes, and influencing.